Health of Antarctic Wildlife A Challenge for Science and Policy - Kerry, Knowles R.; Riddle, Martin (Springer Berlin Heidelberg : Imprint: Springer, 2009)
This book provides a broad assessment of the health of Antarctica's birds and seals. It is set against the background of available scientific and environmental information and the political and administrative processes in place. 17 chapters are presented in two parts: Wildlife Disease consists of reviews, case studies and health assessments. External Factors covers the environmental, administrative and legal aspects. The term health is used in its widest sense to encompass the normal state and those factors which detract from it including both infectious and non-infectious causes. A must for veterinary and biological scientists, policy makers and administrators whose job it is to protect Antarctica's wildlife against the introduction or spread of diseases by human activities.